Job Rotation, Job Promotion, and Employee Performance: Does Job Satisfaction Matter? - Desi Sukmawati; Akhmad Darmawan; Sri Wahyuni; Erny Rachmawati (Research Synergy Foundation, 2026)
Understanding the elements that affect employee performance is essential for organizations seeking to sustain productivity and preserve their competitive edge. This research investigates how job rotation and job promotion influence employee performance, with job satisfaction serving as the mediating factor, focusing on employees of PT. BPR BKK Jateng. A total of 140 employees took part as respondents, and the data were processed through Structural Equation Modeling using the Partial Least Squares SEM PLS approach. The findings reveal that job rotation and job promotion both exert significant positive impacts on employee performance, with job satisfaction acting as a partial mediator in these relationships. All proposed hypotheses were supported, confirming that fair, transparent, and motivating organizational practices enhance employee satisfaction and performance. Job promotion was found to have a greater direct effect beta = 0.538 on job satisfaction compared to job rotation beta = 0.315. However, job rotation was found to have the greatest direct effect beta = 0.361 on employee performance, compared to job promotion beta = 0.237 and job satisfaction beta = 0.311. These results emphasize the vital role of strategic human resource practices in promoting a motivated and high-performing workforce.